Lithium Electrochemical Tuning Engineering in an Aqueous System of LiCoO2 for Enhanced Oxygen Evolution Activity. Issue 4 (1st April 2023) - Yang, Jun; Tang, Dan; Liu, Yang; Li, Wenzhang; Li, Jie
Abstract : LiCoO2 is a promising catalyst for oxygen evolution reaction (OER), yet its OER activity is still unsatisfactory. Here, the delithiated LiCoO2 nanoparticles (NLCO- x cycle) are prepared via a new lithium electrochemical tuning in an aqueous two-electrode system for promoting OER in alkaline solutions. As a result, quantitative deintercalation of Li + can be achieved through an aqueous two-electrode system and the OER performance of NLCO-5 cycle is significantly improved over that of pristine LiCoO2, with a low overpotential of 365 mV at 10 mA cm −2, a small Tafel slope of 55 mV dec −1, and low charge transfer resistance. Performance improvement results from electrochemical delithiation tuning the electronic structure of LiCoO2 . The Li + deintercalation process is accompanied by the partial oxidation of Co 3+ to Co 4+ and the increase of oxygen vacancies, which is associated with the enhanced intrinsic activity of the catalyst. This work paves a simple avenue for reasonable design of effective oxygen electrocatalysts by electrochemical tuning in aqueous systems.